A Criminological Review of Children as Perpetrators of Robbery from the Perspective of Law No. 12 of 2012 Concerning the Juvenile Criminal Justice System - Soni Rasta; Ferawati Royani; Widya Timur (JURNAL HUKUM SEHASEN, 2026)
This study examines the criminological factors that encourage children's involvement in muggings and the application of the Juvenile Criminal Justice System (JCS) to muggings, based on Law Number 11 of 2012. The research method used is normative juridical, with a statutory and conceptual approach. The results indicate three dominant, interrelated factors: first, the influence of social interactions and peer groups, as explained in Edwin H. Sutherland's Differential Association Theory; second, family dysfunction, which weakens children's social bonds, as explained in Travis Hirschi's Social Control Theory; and third, school dropout and unemployment, which encourage illegal behavior, as explained in Robert K. Merton's Anomie Theory. The normative application of the Juvenile Criminal Justice System (JCS) has provided a comprehensive legal framework with a restorative justice approach, aligned with Social Control Theory, to strengthen children's social bonds through rehabilitation and reintegration. However, its implementation still faces normative, infrastructural, and paradigmatic obstacles that require multi-level reform to close the gap between das sollen and das sein.